Penggunaan Model Pembelajaran Probing prompting Sebagai Upaya Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Pembelajaran Sosiologi di Kelas X SMA Pembangunan Laboratorium UNP - Hafizh Syahli Putra; Ike Sylvia (Universitas Negeri Padang, 2022)
This research is motivated by the low critical thinking skills of students in class X Social Sciences 3 SMA UNP Laboratory Development. Based on this, an innovative and creative learning model is needed so as to encourage students to think critically by using the Probing prompting learning model. The purpose of this study was to analysis the effect of the Probing prompting model on students' critical thinking skills. This research is a classroom action research carried out in two cycles. The data collection technique of this research used observation, tests and documentation. The theory that is suitable for this research is Ausubel's cognitive theory. Based on the results of research conducted by researchers at the UNP Laboratory Development High School, the percentage results in the first cycle of 41.32% increased in the second cycle of 70.00% from the results of the second cycle percentage in this study showed an increase in students' critical thinking. Therefore, this use can answer the question of this research in improving the critical thinking of class students.